2019
DOI: 10.3906/sag-1904-41
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 levels in hypothyroidism and its relationship with subclinical atherosclerosis

Abstract: Background/aim: The aim of this study is to evaluate the relationship between serum fatty acid binding protein 4 (FABP4) levels and carotid intima media thickness (CIMT) in patients with hypothyroidism. Materials and methods: Forty subclinical hypothyroidism patients, 40 overt hypothyroidism patients, and 40 healthy controls were enrolled in the study. Blood pressure, body mass index, CIMT, fasting blood sugar, creatine, alanine aminotransferase, lipid parameters, insulin, free thyroxine, triiodothyronine, thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As for the higher prevalence of coronary artery disease, the association between hypothyroidism and increased cardiovascular risk is controversial when thyroid-stimulating hormone (TSH) is normal (Decandia F, 2018). Nonetheless, it was demonstrated that patients with underlying hypothyroidism with a poor disease control have a worse lipidic profile and a higher prevalence of atherosclerosis, since thyroid hormones regulate lipid metabolism, especially TSH (Kotwal A, 2020;Tan M, 2019;Delitala AP, 2017). At the same time, it is well established that a key-factor for adverse cardiovascular events prevention in patients with hypothyroidism is the achievement of symptom control, as well as levels of TSH and T4…”
Section: Discussionmentioning
confidence: 99%
“…As for the higher prevalence of coronary artery disease, the association between hypothyroidism and increased cardiovascular risk is controversial when thyroid-stimulating hormone (TSH) is normal (Decandia F, 2018). Nonetheless, it was demonstrated that patients with underlying hypothyroidism with a poor disease control have a worse lipidic profile and a higher prevalence of atherosclerosis, since thyroid hormones regulate lipid metabolism, especially TSH (Kotwal A, 2020;Tan M, 2019;Delitala AP, 2017). At the same time, it is well established that a key-factor for adverse cardiovascular events prevention in patients with hypothyroidism is the achievement of symptom control, as well as levels of TSH and T4…”
Section: Discussionmentioning
confidence: 99%
“…26 Nonetheless, it was demonstrated that patients with underlying hypothyroidism with a poor disease control have a worse lipidic profile and a higher prevalence of atherosclerosis, since thyroid hormones regulate lipid metabolism, especially TSH. 27,28,29 At the same time, it is well established that a key-factor for adverse cardiovascular events prevention in patients with hypothyroidism is the achievement of symptom control, as well as levels of TSH and T4 within the reference values with the use of hormonal replacement therapy. 30 Another hypothesis to explain the higher frequency of coronary artery disease is the higher prevalence of chronic kidney disease, which is associated with increased cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Median IMT was higher in SH subjects than in euthyroid ones (p<0.0001). Tan et al (24) have found that CIMT is higher in patients with subclinical and overt hypothyroidism than healthy controls (p=0.042 and p<0.001, respectively), concluding that there is a positive correlation between CIMT and TSH. They also found that high thyroglobulin levels were an independent factor that increased CIMT.…”
Section: Thyroid Dysfunction and Carotid Artery Atherosclerosismentioning
confidence: 98%